Small business clustering technologies : applications in marketing, management, IT and economics - MacGregor, Robert C., 1951-; Hodgkinson, Ann. (Hershey, PA : Idea Group Pub., 2007)
"This book examines the development and role of small business clusters from a variety of disciplines : economics, marketing, management and information systems. It gathers perspectives from varied disciplines and countries, extending current knowledge by emphasizing the pressure that international competition and IT have on the geographic structure of clusters, possibly leading to a new 'a-spatial' option developing"--Provided by publisher.
Includes bibliographical references and index.
1
Keywords: EMBA; MOT; Small business -- Management; Strategic alliances (Business) -- Management; Business networks -- Management; Cluster analysis